The Dynamics of Marriage between Hindus and Non-Hindus in Medan - S. Siwaji Raja (International Journal of Interreligious and Intercultural Studies, 2025)
The aim of this research is to find out and study the process and implications of the dynamics of marriage between Hindus and Non-Hindus on the religious, social and cultural life of society in Medan. The research results are the process of dynamic marriage between Hindus and Non-Hindus in Medan is a complex journey involving various important stages, including 1) Legal Change, which is characterized by the context of interfaith marriage before the Marriage Law, then the emergence of the Marriage Law and the regulation of marriage according to Hindu Law. 2) Marriage Dynamics Process, the process that occurs between marriages between Hindus and Non-Hindus in Medan begins from the introduction stage, the conversion decision stage, the marriage preparation stage, and the marriage implementation stage. The implications of the dynamics of marriage between Hindus and Non-Hindus on 1) Religious Life which includes redefinition of identity and religious adaptation. 2) Social Life which includes family dynamics and adaptation to social life. 3) Cultural Life which includes openness in cultural adaptation and transformation of cultural identity.